Persistent Long-Term Structural, Functional, and Metabolic Changes After Stress-Induced (Takotsubo) Cardiomyopathy. Issue 10 (6th March 2018) - Scally, Caroline; Rudd, Amelia; Mezincescu, Alice; Wilson, Heather; Srivanasan, Janaki; Horgan, Graham; Broadhurst, Paul; Newby, David E.; Henning, Anke; Dawson, Dana K.
Abstract : Background: Takotsubo cardiomyopathy is an increasingly recognized acute heart failure syndrome precipitated by intense emotional stress. Although there is an apparent rapid and spontaneous recovery of left ventricular ejection fraction, the long-term clinical and functional consequences of takotsubo cardiomyopathy are ill-defined. Methods: In an observational case-control study, we recruited 37 patients with prior (>12-month) takotsubo cardiomyopathy, and 37 age-, sex-, and comorbidity-matched control subjects. Patients completed the Minnesota Living with Heart Failure Questionnaire. All participants underwent detailed clinical phenotypic characterization, including serum biomarker analysis, cardiopulmonary exercise testing, echocardiography, and cardiac magnetic resonance including cardiac 31 P-spectroscopy. Results: Participants were predominantly middle-age (64±11 years) women (97%). Although takotsubo cardiomyopathy occurred 20 (range 13–39) months before the study, the majority (88%) of patients had persisting symptoms compatible with heart failure (median of 13 [range 0–76] in the Minnesota Living with Heart Failure Questionnaire) and cardiac limitation on exercise testing (reduced peak oxygen consumption, 24±1.3 versus 31±1.3 mL/kg/min, P <0.001; increased VE/VCO2 slope, 31±1 versus 26±1, P =0.002). Despite normal left ventricular ejection fraction and serum biomarkers, patients with prior takotsubo cardiomyopathy had impaired cardiac deformation indices (reduced apical circumferential strain, −16±1.0 versus −23±1.5%, P <0.001; global longitudinal strain, −17±1 versus −20±1%, P =0.006), increased native T1 mapping values (1264±10 versus 1184±10 ms, P <0.001), and impaired cardiac energetic status (phosphocreatine/γ-adenosine triphosphate ratio, 1.3±0.1 versus 1.9±0.1, P <0.001). Conclusions: In contrast to previous perceptions, takotsubo cardiomyopathy has long-lasting clinical consequences, including demonstrable symptomatic and functional impairment associated with persistent subclinical cardiac dysfunction. Taken together our findings demonstrate that after takotsubo cardiomyopathy, patients develop a persistent, long-term heart failure phenotype. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT02989454. Abstract : Supplemental Digital Content is available in the text.